SELF-ASSESSMENT OF HEALTH IN MEN AND WOMEN OF THE OPEN POPULATION OF THE MEDIUM-URBANIZED CITY OF WESTERN SIBERIA: GENDER PECULIARITIES - M. M. Kayumova; A. M. Akimov; T. Yu. Gorbunova; V. V. Gafarov (Сибирский научный медицинский журнал, 2019)
Attitude to health is a complex of social and medical aspects that reflect the subjective health self-assessment of (SZ) by the population, awareness of risk factors (RF) of non-communicable diseases, as well as the level of population involvement in the process of health promotion. A separate category among these parameters is the health selfassessment as an indicator that closely correlates with the human physical health. The aim of the study was to determine the gender characteristics of self-assessment of health status in the open population of the mid-urbanized city of Western Siberia. Material and methods. An one-time epidemiological study was conducted as part of cardiac screening for an open urban population of 25–64 years old among males and females of working age (on the model of Tyumen). The study of health self-assessment, physical complaints, as well as health care evaluation was conducted using a standard questionnaire WHO «MONICA-psychosocial» «Knowledge and attitude to own health». Results. In the open population of the middle urbanized city of Western Siberia, the extremely low men health self-assessment, compared with women, prevails in the older group of 55–64 years old. In the female population the negative health self-assessment and physical complaints totally prevail in young and mature age. Approximately 10 % of the Tyumen population determined adequate own health care (predominantly women of 35–44 years old); men aged 25–34 show a greater desire for own health care. Conclusion. A subjective-objective indicator of the population health, where the health self-assessment holds a unique position, requires active study in populations and can serve as a scientific basis for the development and formation of socially oriented preventive programs that take into account gender and age characteristics and risks.